Diagnosis and Pharmacological Management of Small Intestinal Bacterial Overgrowth in Children with Intestinal Failure - Bushra A Malik; Yuan Y Xie; Eytan Wine; Hien Q Huynh (Canadian Journal of Gastroenterology)
The present article provides a general overview of the possible diagnostic procedures available for the management of small intestinal bacterial overgrowth in pediatric patients with intestinal failure. The focus is to address current diagnostic tools and understand their associated advantages and disadvantages based on a literature search. Culture of small intestinal aspirates, noninvasive breath tests and an emerging interest in quantitative bacterial DNA fingerprinting are discussed. Proper management is critical for preventing the recurrence of small intestinal bacterial overgrowth and its related complications. Antibiotic prophylaxis is one approach to the treatment of bacterial overgrowth in intestinal failure patients. Although treatment trials can be challenging in such a vulnerable population, more investigative clinical studies examining early diagnosis, more effective control of recurrence and the prevention of associated complications must be conducted.